Taxonomic diversity of racerunners with descriptions of two new Eremias species (Sauria: Lacertidae) from Central Iran - Orlova, Valentina F.; Rasegar-Pouyani, Eskandar; Rajabizadeh, Khosrow; Nabizadeh, Hossein; Poyarkov, Nikolay A.; Melnikov, Daniel A.; Nazarov, Roman A. (Zootaxa, 2023)
We provide a diversity assessment of Iranian species of the genus Eremias based on the cytochrome oxidase I mtDNA gene fragment. We analyzed 93 genetic samples from the entire distribution of the Eremias fasciata species complex in Iran and surrounding regions, along with morphological data to support the description of two new species from Central Iran. We hypothesize that the diversification of the Eremias fasciata species complex was largely influenced by the fragmentation of sand massifs in the region. This same hypothesis has been used to explain the high level of endemism among the sand-dwelling species of reptiles along the Iranian Plateau in the same area. The two new species described herein can be distinguished from other congeneric species by their phylogenetic position and a combination of morphological characters. We use these data to discuss the taxonomy of Eremias based on morphology, habitat choice, and genetic data.